Knowledge about sexuality and contraceptive methods in highschool students - Jerónimo Maturana, Carlos Alberto (2009)
Introduction: There has always been intesrest in studying sexual behaviour of teenagers. Objective: To assess knowledge, attitudes, and practices regarding sexuality and contraceptive methods in 4th and 5th grade highschool students in downtown Ica. Materials and Methods: A descriptive cross-sectional study was performed by interviewing 489 4th and 5th grade highschool students in downtown Ica during 2002. Results: Nearly half the interviewees (50.5% [247]) were female, and their mean age was 15.61 years. Two hundred and forty two (49.5%) were male, and their mean age was 15.81. Nearly forty eight per cent (47.6%) of the students declared that they spoke about sex with their parents. Nearly one third (34.6%) of all students pointed out that their main information source about sexuality was their mothers, and for 28.6% it was school teachers. Seven out of ten students (72.6%) perceived their knowledge abour sex was fair, and 90.0% declared they knew about contraceptive methods; while 93.5% declared they may use them in case of sexual intercourse, being condoms the most widely preferred method (62.4%). Six out of ten students (61%) declared they had a boy/girl friend, and 27% (132) declared thay they already had a sexual expèrience. Out of them, 76.5% declared using condoms regularly for sexual intercourse, and 47% pointed out that condoms were difficult for using.   Conclusions: Interviewed high school students have adequate knowledge about sexuality and contraceptive methods, and they are willing to use them, but this must turn into adequate sexuality practices in the future, improving their knowledge on contraceptive methods.